Perbandingan EQ-5D-5L dan SF-6D Untuk Mengukur Index Utility Kesehatan Pada Populasi Umum di Yogyakarta - Tri Murti Andayani; Dwi Endarti; Susi Ari Kristina; Anindya Rahmawati (Faculty of Pharmacy, Universitas Gadjah Mada)
The EuroQuality of life-5 dimension 5 level (EQ-5D-5L) and Short Form-6 Dimension (SF-6D) are the most widely used generic instruments for assessing utility as an outcome parameter in pharmacoeconomic studies. Different instruments cause different utility values and influence the decision making. The purpose of this study was to compare the utility score index measured using EuroQuality of life-5 dimension 5 levels (EQ-5D-5L) and Short Form-6 Dimension (SF-6D) in general population. The study was conducted cross sectional design in general population in the Yogyakarta. EQ-5D-5L and SF-6D questionnaires were given to 470 respondents to measure the utility score index. Differences of utility index scores based on demographic characteristics were analyzed using Mann Whitney and Kruskal Wallis test, while correlations between EQ-5D and SF-6D domains with utility scores were analyzed using Pearson Correlation. Limits of agreement were described by Bland and Altman Plot. The results of the study showed the utility scores measured using EQ-5D-5L, EQ-VAS, and SF-6D were 0.944 (SD = 0.093), 0.829 (SD = 0.089) and 0.915 (SD = 0.081) respectively. EQ-5D-5L and EQ-VAS can distinguish utility values based on age. There is a strong correlation (> 0.700) between the domain of mobility and pain with the EQ-5D-5L utility index, and the domain of physical function and pain with the SF-6D utility index. Ceiling effect of EQ-5D-5L (59%) is greater than SF-6D (22.4%). The Bland and Altman plot shows the difference in utility scores of EQ-5D-5L with SF-6D, SF-6D with EQ-VAS, and EQ-5D-5L with VAS, respectively at the limit of agreement 92.98%, 96 , 38%, and 95.74%. EQ-5D-5L can distinguish utility scores based on age, but showed higher ceiling effect. Both EQ-5D-5L and SF-6D showed a strong correlation between the domain of mobility (physical function) and pain with the utility score.